What Democracy Does (and Doesn't Do) for Basic Services: School Fees, School Inputs, and African Elections. (22nd November 2013) - Harding, Robin; Stasavage, David
<x content-type="archive" xml:space="preserve">Abstract</x> Does democracy affect the provision of basic services? We advance on existing empirical work on this subject by exploring the potential mechanisms through which a democratic transition may prompt a government to alter provision of basic services to its citizens. In an environment of weak state capacity, in which it is difficult for voters to attribute outcomes to executive actions, we suggest that electoral competition is most likely to lead to changes in policies where executive action is verifiable. Considering the context of African primary education as an example, we suggest that electoral competition will therefore give governments an incentive to abolish school fees, but it will have less effect on the provision of school inputs, precisely because executive actions on these issues are more difficult to monitor. We evaluate this claim by approaching it in three different ways, using cross-national as well as individual-level data, including an original data set on primary school fee abolitions. First we show that in Africa, democracies have higher rates of school attendance than nondemocracies. Moreover, evidence suggests that this is primarily due to the fact that democracies are more likely to abolish school fees, not to the fact that they provide more inputs. We then estimate the likelihood that a government will abolish school fees subsequent to an election, taking account of endogeneity concerns involving election timing. Finally, we use survey data from Kenya to provide evidence suggesting that citizens condition their voting intentions on an outcome that a politician can control directly, in this case abolishing school fees, but not on outcomes over which politicians have much more indirect influence, such as local school quality.